A study on the progress of the Diploma in Banking Studies (DIB) graduates of MARA University of Technology Sarawak Branch / Jennifer Tunga Janang … [et.al.] - Janang, Jennifer Tunga; Wong, Annie Muk Ngiie; Kun, Ambi; Hwa, Tee Yong; Voon, Boo Ho (2002)
The Government realized the need to invest in higher education as it contributes towards a well-trained labour force that has the potential and capability to efficiently utilize the capital resources ofthe nation. Under the Eighth Malaysia Plan, the government has allocated 21 per cent ofthe total allocation during the plan period. In Sarawak, more institutions of higher learning are expected to be set up to chum out an increasing number of graduates each year. The mismatch between educational training and workforce requirement may result in wastage and oversupply of manpower in certain skills. Hence, a study to assess the marketability of the graduates is relevant to re-examine the training and investment that the institutions of higher learning have made.